An observational study of sound exposure in a single-room configured neonatal unit (SENSE study). Issue 6 (December 2020) - Best, Kobi; Hughes, Ian; New, Karen; Bogossian, Fiona
Abstract: Aim: To measure sound exposure in an Australian single-room configured, neonatal unit and compare findings to current sound level recommendations. Methods: Sound meters were placed inside 51 internal environments (incubators or open cots), and within the surrounding environment of each occupied single room between September 15 and October 28, 2015. One-second incremental monitoring of decibels on an A-weighted scale (dBA), occurred over a minimum of 48 h. Results: All equivalent continuous sound pressure levels (Leq ) were significantly higher than the recommended 45 dBA for both incubators and open cots. Maximum sound levels (Lmax ) were significantly higher than the recommended 65 dBA, peaking at 126.7 dBA inside the incubator and 124.7 dBA inside the open cot. Incubators were observed to have a higher total percentage of time above 45 dBA than open cots for both day (99.84% vs. 75.59%) and night (98.66% vs. 59.56%). Conclusion: Sound levels exceeded the recommended maximum exposure levels outlined by the American Academy of Pediatrics (AAP). The long-term sequelae of adverse sensory exposure on preterm neurodevelopment remains unclear. Renewed attention on factors contributing to increased sound levels in neonatal units needs to be a clinical priority.